2008
DOI: 10.1080/19325037.2008.10599054
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Tailored Messaging in Health Education

Abstract: It is a health education truism that educational material will be more effective when audience characteristics are taken into account. 1 One strategy that has been proposed to best take into consideration pertinent aspects of individuals is referred to as "tailoring" health information based on individual information processing needs. Tailored communication is a combination of information/change strategies intended to reach one specific person, based on characteristics unique to that person, which are related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In addition, while these programs produce clinically significant effects, little data is available as to whether the interventions themselves are being sustained, as would be necessary to decrease disease burden among populations. Further work needs to analyze their cost-effectiveness and possibly investigate methods for integrating these methods into clinical care systems in ways that they will be maintained over time and available to the populations that would most benefit from them (Stellefson, et al, 2008). In addition, few studies sufficiently reported methods for how assessments and feedback were integrated and no study examined or even mentioned graphic/visual and human factors design issues, which may be important moderators of effect in these communication modalities.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, while these programs produce clinically significant effects, little data is available as to whether the interventions themselves are being sustained, as would be necessary to decrease disease burden among populations. Further work needs to analyze their cost-effectiveness and possibly investigate methods for integrating these methods into clinical care systems in ways that they will be maintained over time and available to the populations that would most benefit from them (Stellefson, et al, 2008). In addition, few studies sufficiently reported methods for how assessments and feedback were integrated and no study examined or even mentioned graphic/visual and human factors design issues, which may be important moderators of effect in these communication modalities.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, this technique forces interaction between dentists and parents in obtaining the children’s oral health-related development information [ 7 ], which is then used to provide oral health anticipatory advice matched to each child’s characteristics. This customization of OHE has been shown to increase clients’ interest and positively affect their cognitive responses to the information received [ 28 ]. Cognitive responses stimulated by tailored health messages have been shown to significantly lead to subsequent behavioral intention and actual behavior change [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the steps involved in developing tailored interventions with a high degree of customization could be quite laborious, time‐consuming and expensive (Lairson et al. 2004, Stellefson et al. 2008).…”
Section: Tailored Interventionsmentioning
confidence: 99%